1998
DOI: 10.1007/s001670050107
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of anterior cruciate ligament using the doubled tendon graft technique: an experimental study in rabbits

Abstract: In an attempt to assess reconstruction of the anterior cruciate ligament (ACL) by a new method, 18 New Zealand white rabbits underwent ACL replacement using the medial one-third of the patellar tendon and the semitendinosus tendon, thus partly reproducing the anatomical configuration of the ACL, with the semitendinosus tendon replacing the posterolateral bundle of the ACL and the patellar tendon replacing the anteromedial bundle. The Noulis-Trillat-Lachman test was performed before and after transection of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 29 publications
(32 reference statements)
1
35
0
5
Order By: Relevance
“…The idea of using a two-bundle reconstruction of the ACL in order to recreate its normal structure is not a new one. We are in agreement with other authors as to the fact that reconstruction of the ACL with two tendons presents several advantages [13,17,20]. More recent studies have suggested the reconstruction of both of the two bundles in order to reproduce the functional anatomy of the ACL, not only controlling the anterior subluxation, but also providing rotatory stability [4,5].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The idea of using a two-bundle reconstruction of the ACL in order to recreate its normal structure is not a new one. We are in agreement with other authors as to the fact that reconstruction of the ACL with two tendons presents several advantages [13,17,20]. More recent studies have suggested the reconstruction of both of the two bundles in order to reproduce the functional anatomy of the ACL, not only controlling the anterior subluxation, but also providing rotatory stability [4,5].…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have demonstrated that the material properties of the porcine patellar and flexor digitorum profundus tendons were similar to the human patellar tendon and hamstring tendons, respectively [11]. To improve the results of ACL reconstruction under the aggressive early rehabilitation and to reproduce the complex functional anatomy of the native ACL, many authors recommend the use of double-bundle techniques [9,13,17].…”
Section: Introductionmentioning
confidence: 99%
“…Post-traumatic arthritis was noticed in some of our experimental animals during our previous investigations [19,24], but that could be attributed either to the ACL injury or to the surgical procedure itself. Nevertheless, we have not noticed any such case in our present series.…”
Section: Discussionmentioning
confidence: 99%
“…Average age = 23.7 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) years. The left knee was involved 6 times and the right knee 12 times.…”
Section: Methodsmentioning
confidence: 99%
“…We consider that the developing of an ACL reconstruction technique that use semitendinosus not as a free autograft but as a graft that retains its natural attachment [33][34][35][36] may be more effective than the techniques that use free hamstrings autografts.…”
Section: Discussionmentioning
confidence: 99%